Public Policy Targets in EU Broadband Markets: The Role of Technological Neutrality - Wolfgang Briglauer; Volker Stocker; Jason Whalley (International Telecommunications Society (ITS), 2018)
The European Commission has recently sought to substantially revise how it regulates the telecommunication industry, with a key goal being to incentivise investment in high-speed broadband networks. Ambitious goals have been set regarding the availability and quality of broadband across the European Union, initially in the 'Digital Agenda for Europe' and more recently in its 'Gigabit strategy'. These goals reflect the view of many that there are widespread and significant socio-economic benefits associated with broadband. Our analysis explores the consequence of target setting at a European level, in terms of encouraging investment and picking which technology should be adopted within the context of technological neutrality. We demonstrate that while public policy targets favour specific technologies, especially when the target is defined with regards to fast broadband speeds, the technological choices that occur within a Member State are shaped by the complex and dynamic interaction between a series of path dependencies that may vary significantly across as well as within Member States. Furthermore, taking into account the ecosystem's tremendous evolution, the technological choices that are made within markets reflect both demand and supply uncertainties. To assist with understanding the interaction between those forces that shape, to lesser or greater extent, the choice of one technology over another, we propose a four-phase framework. This framework is not a definitive statement of the relationships that we have identified, but rather serves as a mechanism that illustrates the challenges associated with adopting and then sticking with technological neutrality in policy making.
Keywords: L38; L50; L52; L96; 330; Broadband; technological neutrality; fibre networks; 5G; path dependency; EU public policies